Regulation of Phytohormones on the Growth and Development of Plant Root Hair - Li, Mengxia; Zhu, Yanchun; Li, Susu; Zhang, Wei; Yin, Changxi; Lin, Yongjun (Frontiers in Plant Science, 2022)
The tubular-shaped unicellular extensions of plant epidermal cells known as root hairs are important components of plant roots and play crucial roles in absorbing nutrients and water and in responding to stress. The growth and development of root hair include, mainly, fate determination of root hair cells, root hair initiation and root hair elongation. Phytohormones play important regulatory roles as signal molecules in the growth and development of root hair. In this review, we describe the regulatory roles of auxin, ethylene (ETH), jasmonate (JA), abscisic acid (ABA), gibberellin (GA), strigolactone (SL), cytokinin (CK), and brassinosteroid (BR) in the growth and development of plant root hairs. Auxin, ETH, CK play positive regulation while BR plays negative regulation in the fate determination of root hair cells; Auxin, ETH, JA, CK, ABA play positive regulation while BR plays negative regulation in the root hair initiation; Auxin, ETH, CK, JA play positive regulation while BR, GA, ABA play negative regulation in the root hair elongation. Phytohormones regulate root hair growth and development mainly by regulating transcription of root hair associated genes, including WEREWOLF (WER), GLABRA2 (GL2), CAPRICE (CPC), and HAIR DEFECTIVE 6 (RHD6). Auxin and ETH play vital roles in this regulation, with JA, ABA, SL and BR interacting with auxin and ETH to regulate further the growth and development of root hairs.